Kajian Protein Hewani Untuk Meningkatkan Kadar Hemoglobin Pada Ibu Hamil : Literatur Review - Safitri, Fira Deananta; Rahmawati, Alfiah; Jannah, Muliatul (JIDAN Jurnal Ilmiah Bidan, 2025)
Background: Optimal nutrition during pregnancy, especially adequate intake of animal protein, is essential for maternal and fetal health. Animal protein provides essential amino acids needed for fetal growth and maternal tissue development, as well as heme iron, which is easily absorbed and supports hemoglobin production. Adequate intake helps prevent fetal growth restriction and supports normal birth weight. Nutritional deficiencies can lead to complications such as anemia, low birth weight, and congenital abnormalities, while overnutrition may also pose risks. Therefore, maintaining a balanced intake of nutrients, including animal protein, is crucial. Objective: This literature review aims to analyze the role and effectiveness of animal protein in increasing hemoglobin levels in pregnant women as a strategy to prevent pregnancy-related anemia. Methods: A systematic review was conducted using articles from PubMed and Google Scholar databases, published between 2014–2024. Keywords used included "pregnancy," "anemia," "animal protein," and "nutritional content of animal protein." Based on the selection criteria, 15 articles (14 national and 1 international) were included. Results: Adequate intake of animal protein was found to be effective in increasing hemoglobin levels and preventing anemia during pregnancy. Recommended sources include chicken liver, beef, chicken meat, fish, and eggs, which are rich in essential amino acids, iron, and vitamin B12—nutrients vital for red blood cell production. Conclusion: Regular consumption of animal protein is an important nutritional intervention to prevent anemia in pregnant women. Among various sources, fish consistently shows the highest potential in improving hemoglobin levels, likely due to its high content of heme iron and omega-3 fatty acids.